Biomarkers in Painful Symptomatic Knee OA Demonstrate That MRI Assessed Joint Damage and Type II Collagen Degradation Products Are Linked to Disease Progression - Sofat, Nidhi; Ejindu, Vivian; Heron, Christine; Harrison, Abiola; Koushesh, Soraya; Assi, Lena; Kuttapitiya, Anasuya; Whitley, Guy S.; Howe, Franklyn A. (Frontiers in Neuroscience, 2019)
Background: Osteoarthritis (OA) is the most prevalent arthritis worldwide, but the evolution of pain in relation to joint damage and biochemical markers are not well understood. We evaluated the relation between clinical pain measures and evoked pain in relation to structural damage and biochemical biomarkers in knee OA. Methods: A cross-sectional study in people with knee OA and healthy controls was conducted. A total of 130 participants with advanced OA requiring total knee replacement (TKR) (n=78), mild OA having standard care (n=42) and non-OA controls (n=6), with 4 drop-outs were assessed. Pain scoring was performed by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC_P) and the Visual Analog Scale (VAS). Pain sensitisation was assessed by pain pressure thresholds (PPT). Knee MRI assessed joint damage using the MRI Knee Osteoarthritis Score (MOAKS). Overall MOAKS scores were created for Bone Marrow Lesions (BML), Cartilage Degradation (CD) and effusion/Hoffa synovitis (tSyn). Type II collagen cleavage products (CTX-II) were determined by ELISA. Results: The advanced OA group had a mean age of 68.9 +/- 7.7 years and the mild group 63.1 +/-9.6. The advanced OA group had higher levels of pain, with mean WOMAC_P of 58.8 +/- 21.7 compared with the mild OA group of 40.6 +/-26.0. All OA subjects had pain sensitization by PPT compared with controls (p<0.05). WOMAC_P correlated with the total number of regions with cartilage damage (nCD) (R=0.225, p=0.033) and total number of BMLs (nBML) (R=0.195, p=0.065) using body mass index (BMI), age and Hospital Anxiety and Depression Scale (HADS) as covariates. Levels of CTX-II correlated with tSyn (R=0.313, p=0.03), nBML (R=0.252, p=0.019), number of osteophytes (R=0.33, p=0.002) and nCD (R=0.218, p=0.042), using BMI and age as covariates. A multivariate analysis indicated that BMI and HADS were the most significant predictors of pain scores (p<0.05). Conclusion: People with both mild and advanced OA show features of pain sensitisation. We found that increasing MRI-detected joint damage was associated with higher levels of CTX-II, suggesting that increasing disease severity can be assessed by MRI and CTX-II biomarkers to evaluate OA disease progression.